PENDIDIKAN INDONESIA PADA MASA PRASEJARAH DAN HINDU-BUDHA - PRASETYO, OKHAIFI (Program Studi Pendidikan Sejarah - Universitas Samudra, 2021)
The journey of the development of education is very long from before independence can be traced back to prehistoric and Hindu-Buddhist times. This study aims to discuss what and how the state of education in Indonesia, especially in the Prehistoric and Hindu-Buddhist periods. The method used in this research is the historical research method in prehistoric times or what is known as the preaksara era. In this era, humans are still learning from nature with what they need. There are three periods of educational development at this time, namely Meganthropus, Pithecanthropus, Homosapien. Then education in the Hindu and Buddhist era was through the spread of religion, which in the past there were no schools that we see today. In the past, monks and scholars became teachers without being given worldly rewards. They also get education from their families too; if the family is a farmer, their children will learn from a father, and the knowledge they get is only for their children. They learn skills, chivalry, and so on. The son of a king has his own place to study, which is called Pura; so far, his sons and daughters have learned about the science of state administration, manners, and martial arts. The material taught is not only general in nature but also studies spiritual and religious sciences.